Is Adolescent Physical Literacy Linked to Their Mental Health? - Nurjanah, Nurjanah; Mubarokah, Kismi; Haikal, Haikal; Setiono, Oki; Belladiena, Alfiena Nisa; Muthoharoh, Nor Amalia; Rahma, Nis Syifa’ur; Iqbal, Muhammad; Nurmandani, Ririn; Ratna Wulan, Widya; Geets-Kesić, Marijana; Savicevic, Anamarija Jurcev (Universitas Airlangga, 2025)
Background: More than 10% of adults in Indonesia experience mental and emotional disorders. Previous research has concluded that mental health is related to a person's physical literacy. Objectives: This study explores the relationship between physical literacy and mental health among adults in Semarang City, Indonesia, emphasizing the mediating role of various physical literacy domains. Methods: This observational study used a cross-sectional design with 610 participants chosen by stratified selection. Physical literacy and mental health were evaluated using the Perceived Physical Literacy Questionnaire (PPLQ) and the Self-Reporting Questionnaire (SRQ-20), respectively. All data acquired during interviews with trained enumerators were then processed using Stata. The data was then evaluated with the Spearman Rank test. Results: The study included more women than men. They were largely high school and college students who weren't yet married. The respondents' physical literacy remained moderate, while their mental health remained good/free of unhealthy mental issues. Bivariate analysis revealed that higher levels of physical literacy were linked to better mental health outcomes, particularly in the categories of physical ability, knowledge, and motivation. Age and education levels also have a substantial impact on mental health. Conclusions: Physical literacy has a substantial impact on mental health among adults in Semarang City.